THE INFLUENCE OF HR QUALITY ON HEALTH SERVICES IN SIEMPAT RUBE HEALTH CENTER, PAKPAK BHARAT DISTRICT: PENGARUH KUALITAS SDM TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS SIEMPAT RUBE KABUPATEN PAKPAK BHARAT - Padang, Natalia (LPPM UPMI, 2024)
Research The quality of health services at Community Health Centers is a crucial aspect in the public health system, especially in remote areas such as the Siempat Rube Community Health Center in Pakpak Bharat Regency. The quality of this service is very dependent on the quality of Human Resources (HR) within it. This research aims to analyze the influence of HR quality on health services at the Siempat Rube Health Center. The main focus is to evaluate the relationship between the skills, knowledge and attitudes of health workers with patient satisfaction and the effectiveness of health services. The method used in this research is to use a descriptive correlation analysis method using simple linear regression analysis as well as quantitative data and using statistical formulas. And the sample in this research is based on the population obtained from a sample of 100 respondents who are patients at the Siempat Rube Community Health Center, PakpakBharat Regency. The research results show that there is a significant positive relationship between the quality of human resources (including skills, knowledge and attitudes) and patient satisfaction. The skills and knowledge of health workers have a significant impact on service effectiveness, while the attitude of health workers also contributes to patient satisfaction. The quality of human resources has a significant impact on health services at the Siempat Rube Community Health Center. Therefore, improving the quality of human resources through continuous training and education is very important to increase patient satisfaction and the effectiveness of health services. Recommendations for this research include the need for a more intensive HR development program as well as regular evaluation of service quality.